The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1111/ases.12437
|View full text |Cite
|
Sign up to set email alerts
|

Robotic surgery for the upper gastrointestinal tract: Current status and future perspectives

Abstract: More than 4000 da Vinci Surgical Systems have been installed worldwide. Robotic surgery using the da Vinci Surgical System has been increasingly performed in the last decade, especially in urology and gynecology. The da Vinci Surgical System has not become standard in surgery of the upper gastrointestinal tract because of a lack of clear benefits in comparison with conventional minimally invasive surgery. We initiated robotic gastrectomy and esophagectomy for patients with upper gastrointestinal cancer in 2009… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 67 publications
0
19
0
1
Order By: Relevance
“…In Japan, however, Nakauchi et al reported on the initiation in 2009 of robotic gastrectomy and esophagectomy for patients with upper gastrointestinal cancer, and they showed potential advantages of the da Vinci Surgical System in reducing postoperative local complications after gastrectomy and recurrent laryngeal nerve palsy after esophagectomy. However, robotic surgery has the disadvantages of a longer operative time and higher costs than the conventional approach …”
Section: Treatmentsmentioning
confidence: 99%
“…In Japan, however, Nakauchi et al reported on the initiation in 2009 of robotic gastrectomy and esophagectomy for patients with upper gastrointestinal cancer, and they showed potential advantages of the da Vinci Surgical System in reducing postoperative local complications after gastrectomy and recurrent laryngeal nerve palsy after esophagectomy. However, robotic surgery has the disadvantages of a longer operative time and higher costs than the conventional approach …”
Section: Treatmentsmentioning
confidence: 99%
“…Although several groups have reported the feasibility and safety of a wide range of esophagectomy approaches with good short-term outcomes, these reports were all based on retrospective studies with a small number of patients (16). In 2015, Ruurda et al conducted a systematic review of 16 case series, each consisting of 11-118 cases (73); there were 300 cases in total.…”
Section: Short-term Outcomes Of Robot-assisted Esophagectomymentioning
confidence: 99%
“…In a Western series, LLDP was commonly used and some authors tried thoracic anastomosis. In contrast, in an Asian series, the prone or semiprone positions and cervical anastomosis were preferred .…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…These trials will address some of the future perspective of surgical management of gastric GISTs such as the role of robotic surgery and endoscopic resection. Robotic surgery has been increasing performed in the last decade but the current evidence showed that robotic gastric resections have the disadvantages of longer operating time and higher costs than conventional laparoscopic approach (40).…”
Section: Gastric Gists Trial Studiesmentioning
confidence: 99%